The exploitation of crabs by Last Interglacial Iberian Neanderthals: The evidence from Gruta da Figueira Brava (Portugal) - Nabais, Mariana; Dupont, Catherine; Zilhão, João (Frontiers in Environmental Archaeology, 2023)
Hominin consumption of small prey has been much discussed over the past decades. Such resources are often considered to be unproductive in the Middle Paleolithic due to their limited meat yield and, hence, low energy return. However, ethnographic studies suggest that small prey—including shellfish—are a reliable, predictable and by no means marginal resource, and there is increasing evidence for their inclusion in hominin diets during the Middle Paleolithic and even earlier. Gruta da Figueira Brava features a MIS 5c-5b Neanderthal occupation that left behind substantial, human-accumulated terrestrial and marine faunal remains, capped by reworked levels that contain some naturally accumulated, recent Holocene material, namely the remains of small crab species and echinoderms. The brown crab Cancer pagurus (Linnaeus, 1758) predominates in the intact Middle Paleolithic deposit, and reconstruction of its carapace width, based on regression from claw size, shows a preference for relatively large individuals. The detailed analysis of the Cancer pagurus remains reveals that complete animals were brought to the site, where they were roasted on coals and then cracked open to access the flesh.